Society and politics in post civil-war Greece: aspects and dimensions of the associations in the area of Athens, 1949-1967 - Καραγιάννης, Γιάννης (The Greek Review of Social Research, 2016)
In this article we track down and record all associations found at the archives of the Athens Administrative Court of First Instance for the period 1949-1967. By recording them and providing a thematic index of these associations, we were able to detect the various dimensions of «civil society» in post civil-war Greece, whilst at the same time formulating questions related to the nature and dynamics of Greek society. Furthermore, this study gives the opportunity to explore further the relationship between politics and society, state and «civil society».